PENGARUH ABDOMINAL STRETCHING EXERCISE TERHADAP PENURUNAN DYSMENORHEA PADA REMAJA PUTRI DI SMA MUHAMMADIYAH RAMBAH - Wahyuny, Romy; Nurhafni, Nurhafni; Andriana, Andriana; Nurkhasanah, Siti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Dysmenorrhea is pain, cramps in the lower abdomen, and is often accompanied by other symptoms such as sweating, headaches, nausea, diarrhea, and trembling. One way to treat Dysmenorrhea is with relaxation techniques, namely Abdominal Stretching Exercise. Abdominal Stretching Exercise is a muscle stretching exercise, especially in the abdomen, which is done for 20 minutes. The purpose of this study was to determine the Effect of Abdominal Stretching Exercise on Reducing Dysmenorrhea in Adolescent Girls at SMA Muhammadiyah Rambah. This research method uses a Pre-Experimental research design with a one group pretest-posttest approach. This research was carried out in September-October 2024. Sampling using purposive sampling was 20 respondents. The instrument used was the Numeric Rating Scale (NRS) Pain Level Measurement Sheet. The results of this study were analyzed from 20 respondents before doing Abdominal Stretching Exercise who experienced mild Dysmenorrhea, there were 9 respondents, moderate Dysmenorrhea 9 respondents, and severe Dysmenorrhea 2 respondents. The results of the T-dependent statistical test ρ value (0.001) < α (0.05) then (H0) is rejected and (Ha) is accepted, meaning there is an Effect of Abdominal Stretching Exercise on Reducing Dysmenorrhea in Female Adolescents at SMA Muhammadiyah Rambah. It is expected that female adolescents who experience Dysmenorrhea can do Abdominal Stretching Exercise to reduce Dysmenorrhea.Keywords: Adolescents, Abdominal Stretching Exercise, Dysmenorrhea